ANALISIS Pengaruh Current Ratio, Size, Debt To Equity Ratio, dan Total Asset Turnover Terhadap Dividend Yield dengan Return On Asset Sebagai Variabel Intervening - Prakoso, Prio Galih Raga; Chabachib, Mochammad (Diponegoro Journal of Management, 2016)
Financial performance has become one of the most important issues for investors before they investing their fund inside the company. There is so many factors affect the financial performance and affect their decisions. The sample used in this research consists of 25 manufacturing companies listed on the Indonesian Stock Exchange (IDX) 2010-2014. This study used the purposive sampling methods. Data obtained from the Indonesian Capital Market Directory (ICMD) and Annual Report. Data analysis method used is multiple linear regression analysis and also path analyisis for analyze the indirect effect of independent variables.The result indicates that CR, and TATO has significant positive effect on ROA, while DER has significant negative effect on ROA, while Size is the only one variable that has no effect on ROA. In the second regression, the result indicates that ROA, Size, and TATO has significant positive effect on Dividend Yield, while CR and DER has significant negative effect. More further, path analysis result indicates that CR and TATO has significant positive effect on Dividend Yield through intervening variables (ROA) while Size and DER has no significant effect on Dividend Yield through intervening variables (ROA).